A model test study to optimize the ventilation system of a long expressway tunnel. Issue 207 (December 2020) - Liu, Kaiyun; Guo, Jiaqi; Wan, Liangyong; Xu, Chong
Abstract: Ventilation during long highway tunnel operation plays a key role in environmental health, energy savings and reducing consumption. A ventilation model test platform, based on similarity theory, was designed and built with a 1/50 transverse length scale to simulate different fan on/off states for the Fenshuiling long expressway tunnel. The test platform was used to perform a systematic shut-off of jet fans in left and right bores during Fenshuiling tunnel operation. The wind speed distribution at measurement sites in the left and right bores was determined, and the influence law of the number of jet fans in the shut-off state on the wind speed was obtained. The test results showed that the air speed distribution patterns in the tunnel were reasonable. The test results were used to optimize the original ventilation design of the Fenshuiling tunnel. A field test of the ventilation performance during tunnel operation showed that the carbon monoxide (CO) concentration in the tunnel was below that stipulated for long tunnels in the Guidelines for Design of Ventilation of Highway Tunnels. The optimized ventilation system met the short-term airflow requirements for the left and right bores. This study provides important guidance for the design of ventilation systems for long highway tunnels. Highlights: A physical model test platform was developed to simulate the ventilation system in the Fenshuiling long tunnel. The model platform was used to carry out ventilation test simulations for the Fenshuiling tunnel. The model results were used to optimize the original ventilation design of the Fenshuiling tunnel. The modified ventilation system was verified by field test results performed during operation of the Fenshuiling long tunnel.